The novel organoselenium compound 4aa ameliorates osteoporosis by modulating gut microbiota composition and fecal metabolite profiles - Hu, Chaoming; Zhang, Yichi; Wu, Yao; Tu, Junhao; Yi, Mengjia; Mao, Yixin; Chen, Yang; Sun, Xiaoyu; Song, Zengqiang; Huang, Shengbin; Zhao, Shufan; Li, Bin (Frontiers in Endocrinology, 2025)
BackgroundThe gut microbiota plays a key role in regulating bone homeostasis. Our previous work demonstrated that the novel organic selenium compound β-trifluoroethoxy dimethyl selenide (4aa alleviates osteoporosis; however, its mechanism remains unclear.MethodThe cytotoxicity of 4aa in osteoblast (MC3T3-E1) and osteoclast precursor (RAW264.7) cells was evaluated using CCK-8 assays. Ovariectomized (OVX) and sham-operated mice were treated with various concentrations of 4aa for 8 weeks, including a subgroup pretreated with antibiotics (ABX) to deplete the gut microbiota. Femoral bone structure was assessed by micro-computed tomography (micro-CT), osteoclast numbers were quantified, gut microbial composition was analyzed via 16S rRNA sequencing, and fecal metabolites were profiled using LC-MS/MS.Results4aa concentrations below 20 μM were non-cytotoxic to MC3T3-E1 and RAW264.7 cells. In vivo, 4aa significantly improved femoral bone mass and trabecular microarchitecture in OVX mice. Gut microbiota analysis revealed increased relative abundances of Dubosiella, Akkermansia, and Bacillus spp following 4aa administration. Metabolomic profiling identified marked alterations in citronellal, tyrosol, kaempferol, leukotriene D4, clomipramine, and phenol sulfate level. Moreover, 4aa elevated butyric acid levels and reduced the accumulation of α-ketoisovaleric acid (α-KIV), contributing to the inhibition of osteoclast differentiation.Conclusion4aa prevents estrogen deficiency-induced bone loss by modulating gut microbial composition and function. These findings support the therapeutic of 4aa as a microbiota-targeted therapeutic strategy for osteoporosis management.